Delivery of nutritional management services to people with amyotrophic lateral sclerosis (ALS). Issue 5 (3rd July 2021) - Halliday, Vanessa; Zarotti, Nicolò; Coates, Elizabeth; McGeachan, Alexander; Williams, Isobel; White, Sean; Beever, Daniel; Norman, Paul; Gonzalez, Sarah; Hackney, Gemma; Ezaydi, Naseeb; Stavroulakis, Theocharis; et al.
Abstract: Objectives: The aim of this study was to investigate how nutritional management services for people with Amyotrophic Lateral Sclerosis (pwALS) are structured in the UK, in order to gain insight into current practice and identify key barriers and enablers to delivering and providing services. Methods : A three-part, sequential mixed-methods study was conducted that comprised (i) a thematic analysis of data from five focus groups (with 47 ALS health professionals from 41 UK organizations and four service user representatives), (ii) a nationwide cross-sectional survey (281 ALS healthcare professionals) and (iii) a freedom of information request (251 organizations). Results : UK nutritional management services for pwALS are coordinated from specialist ( n  = 22) and non-specialist care centers ( n  = 89), with national variability in the organization and delivery of services. Multidisciplinary working was highlighted to facilitate the coordination of nutritional care. However, the need to provide evidence-based continuing education for HCPs was evident. Overall, the lack of clear guidelines on the nutritional management of people with ALS was identified as a key barrier to the delivery of effective nutritional care, as was the lack of transparency and consistency in the commissioning of nutritional services. Further concerns over the timeliness of the dietetic intervention and equity of access and provision were raised. Conclusions : Our findings suggest that development of guidelines for nutritional management, particularly at diagnosis and pre-gastrostomy, could drive standardization of high quality nutritional care for pwALS. Such guidance has the potential to reduce inequalities in geographical provision by providing clarity for those commissioning specialist nutrition services.